The measurement accuracy of instrumented ship structures under local ice loads using strain gauges. (March 2021) - Böhm, Angelo Mario; von Bock und Polach, Rüdiger Ulrich Franz; Herrnring, Hauke; Ehlers, Sören
Abstract: Strain gauges are commonly used for the instrumentation of ship structures to measure ice loads on the basis of shear strain differences. Finite Element Analysis (FEA) is used to determine the load–strain relation of the instrumented area by calculating an Influence Coefficient Matrix (ICM). However, the accuracy of the measurement method and the influence of the load location and load length on the accuracy of the load determination are rarely assessed. Consequently, this paper identifies the accuracy of the ICM, discusses which structures are suitable for measurements of shear strain differences and presents possible improvements regarding these measurements. As load cases are systematically varied over a finite element model, the external load is recalculated based on the resulting shear strains. The number of strain gauges used for the measurement of shear strains has a significant impact on the ICM. For common instrumentation it was found that the ice load can only be accurately determined, if the ice load acts within the instrumented area. To overcome this limitation, an approach to determine the load location is presented among further recommendations.